The Impact of Agricultural Practices on the Environmental Management of Nyarubuye Sub-County Kisoro District. - Akampurira, Hellen (Kabale University, 2024)
The research focused on examining the impact of agricultural practices on environmental management in the Nyarubuye sub-county, Kisoro district. The study aimed to identify common agricultural practices in the Nyarubuye sub-county, investigate activities that degrade the environment, and assess the effects of these practices on environmental management. Chapter two critically reviewed theoretical and empirical literature on land use practices as the independent variable and environmental management as the dependent variable. Chapter three detailed the implementation of data collection methods, employing both qualitative and quantitative approaches. Simple random sampling was used to ensure equal chances for participants, while purposive sampling targeted specific respondents. Chapter Four presented the field findings, interpreting results based on the study's objectives. Chapter Five summarized the findings, offered conclusions, and provided recommendations on the impact of agricultural practices on environmental management in the Nyarubuye sub-county, Kisoro district.